The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1002/jemt.20243
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced differential apoptosis in the central nervous system of the sturgeon (Acipenser shrenckii)

Abstract: Hypoxia is a frequent challenge to aquatic vertebrates as compared with that for their terrestrial counterparts. All vertebrates respond to hypoxia in a similar, but not identical manner, indicating that these responses appeared early in the evolution of vertebrates. The aim of this study is to find out the effects of hypoxia on apoptosis in the central nervous system (CNS) of sturgeon, an archaic fish. With the regional specialization of the CNS, we hypothesize that if cell death does occur, the response will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…During apoptosis, caspase-activated endonucleases cause doublestranded DNA breaks. Staining of double or single DNA strand breaks by terminal transferase mediated dUTP nick end labelling technique (TUNEL) has been used as an indicator for apoptotic conditions under several environmental conditions in fishes (Piechotta et al, 1999;Imajoh et al, 2005;Lu et al, 2005). Changes in normal intestinal cell renewal has been suggested as early indicators for abnormal or toxic conditions to the GI tract (Uni et al, 1998;Berntssen et al, 2003Berntssen et al, , 2004Sheen-Chen et al, 2003;Hemre et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…During apoptosis, caspase-activated endonucleases cause doublestranded DNA breaks. Staining of double or single DNA strand breaks by terminal transferase mediated dUTP nick end labelling technique (TUNEL) has been used as an indicator for apoptotic conditions under several environmental conditions in fishes (Piechotta et al, 1999;Imajoh et al, 2005;Lu et al, 2005). Changes in normal intestinal cell renewal has been suggested as early indicators for abnormal or toxic conditions to the GI tract (Uni et al, 1998;Berntssen et al, 2003Berntssen et al, , 2004Sheen-Chen et al, 2003;Hemre et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, caspase-3 was differentially expressed during zebrafish development [47]. Subsequent studies confirmed a role for caspase-3 in mediating stress-induced cell death in Atlantic salmon exposed to hyperthermia [44], in sea bass (Dicentrarchus labrax L.) in response to bacterial infection [48], in zebrafish exposed to DNA damaging conditions [18,49,50], and in sturgeon (Acipenser schrenckii) during prolonged hypoxia [51]. The importance of caspase-3 in embryonic development was corroborated by showing tissue-and stage-specific expression in Atlantic salmon [44].…”
Section: Fish Caspases Their Activators and Inhibitorsmentioning
confidence: 72%
“…VEGF (vascular endothelial growth factor) immunocytochemistry was performed for tagging neovascularization, and lactic acid dehydrogenase (LDH) immunocytochemistry was used for detecting necrosis. All experiments were performed on paraffin sections of various specimens as described previously 6,13,14 . The TUNEL kit was purchased from Chemicon (Temecula, CA, USA), the VEGF and LDH antibody from Santa Cruz Biotech (California, CA, USA), and the ABC (avidin‐biotin complex testing) immunocytochemistry kit from Zymed (San Francisco, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In humans, it has been reported that intrapartal asphyxia could result in a high percentage (over 30%) of patients developing subsequent malformations of the CNS 1 . Aquatic hypoxia in fish poses an even greater challenge than hypoxia in land vertebrates, and the presence of apoptotic cells has been pronounced in the nervous systems of sturgeons rendered hypoxic 5,6 . In other species of fish, such as the crucian carp, and some freshwater turtles and frogs, the effects of hypoxia have been less obvious 7,8 .…”
Section: Introductionmentioning
confidence: 99%